Dynamics of microbiota in the imported beef primal cuts during storage at different chilled temperatures. Issue 8 (13th July 2022) - Nakamura, Ayaka; Mizuno, Yuri; Takahashi, Hajime; Otomo, Kota; Kuda, Takashi; Kimura, Bon
ABSTRACT: Primal cuts of Australian beef transported by sea were stored under different chilled temperatures (0, 2, and 4 °C) for 6 weeks in different packaging conditions (aerobic or anaerobic packaging). The number of microorganisms and the transition of the microbiota were investigated using culture methods and amplicon sequencing. After 6 weeks of storage, the beef tended to show a high total viable count under aerobic packaging conditions and a high lactic acid bacteria count under anaerobic packaging conditions. The result of amplicon sequencing analysis showed that different beef samples had different predominant bacterial groups. Moreover, at high storage temperatures, Serratia sp. having high putrefactive activity showed increased abundance, while at low storage temperatures, Lactobacillus sp. showed increased abundance. Thus, differences in the packaging conditions and distribution temperatures after import affect the number of bacteria and the type of microorganisms in the Australian beef primal cuts, which may affect their quality. Graphical Abstract: